Novel Double Slope Frequency Shift Chirp Symbol - Lerson Kirasamuthranon; Paramote Wardkein; Jeerasuda Koseeyaporn (IEEE Access, 2024)
One of the most significant concerns in serial digital communication is the synchronization of data bits between the transmitter and receiver. Therefore, the preferred coding symbols should contain an inherited clock signal. The cyclic-shift chirp, which is primarily used in long-range systems, employs a single slope in a symbol, which contains few information for synchronization. Hence, two new forms of cyclic-shift chirp symbols are proposed herein. The associated coding schemes are based on the use of a dual slope within one symbol. Synchronization is inherited in the coding symbol using a dual slope. Additionally, both proposed coding schemes utilize the same decoding technique. The decoded chirp symbol is in the form of a pulse width modulation signal, which can be used for synchronization and retrieving data bits from their duty cycle. The simulation results show that the coding and decoding processes of the proposed coding schemes align with those of a theoretical framework. The error performance analysis for the proposed detection scheme is given and the results of error probability analysis are consistent with the simulation results. Moreover, under a Rayleigh fading channel, the proposed coding schemes provide superior performance compared with other comparable coding schemes.
Keywords: Underwater Acoustics Research; Gait Recognition and Analysis; Civil and Geotechnical Engineering Research